Moral development: pro-social and pro-environmental approaches - Raymundo, Luana Santos (2014)
This study aimed to investigate the pro-social and pro-environmental approaches of the moral development in Psychology. Therefore, a literature review (2005-2010) from studies found in a worldwide referenced database (PsycINFO) was performed. The pro-social approach discussed the moral development in almost the whole human life cycle, analyzing acquisition of virtues and moral judgments. In contrast, the pro-environmental approach focused on adult age, searching for relations between psychosocial variables and the occurrence of a desired behavior. Both approaches are similar in considering altruistic motivations for moral behavior. It was discussed how the pro-environmental approach would benefit from the investigative view of the pro-social approach.